Animation films in the cinemas of Madrid in the interwar period (1916-1939) - Tirado, Gonzalo (Hispania Nova, 2021)
This study investigates the dissemination of animated film productions in Madrid´s cinemas from the first projections reported, around 1916, until the end of the Spanish Civil War. The main objective is to verify whether foreign animation films arrived in Spain on a regular basis and also if Spanish productions were present in cinemas during this period. The sources used are the billboard sections that appear in the newspapers of the time, as well as the magazines specialized in cinema and shows. Based on this, a quantitative analysis of the press boards will be carried out, although within an overall vision, complemented all with the qualitative analysis of other publications of the period.